PEDOT: PSS-based conductive ink for thermal transfer printing and preparation method and application thereof

By adding D-sorbitol, thermoplastic resin and GOPS to PEDOT:PSS-based conductive ink, the shortcomings of existing conductive thermal transfer inks in terms of conductivity, flexibility, stability and durability are solved, and high-performance conductive inks are achieved Ink, suitable for smart electronic textiles and wearable devices.

CN119410200APending Publication Date: 2025-02-11BEIJING INSTITUTE OF GRAPHIC COMMUNICATION
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411534370.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-30
Publication Date
2025-02-11

AI Technical Summary

Technical Problem

Existing conductive thermal transfer inks have shortcomings in electrical conductivity, mechanical flexibility, stability and durability, limiting their application in smart electronic textiles and wearable devices.

Method used

By modifying the PEDOT:PSS-based conductive ink, D-sorbitol, thermoplastic resin and (3-glycidyl propoxy)trimethoxysilane (GOPS) are added to improve its conductivity, flexibility, stability and adhesion.

Benefits of technology

It realizes good conductivity during the thermal transfer process, and significantly improves adhesion and durability on the fabric, forming fabric electrodes with certain conductivity, excellent water washing resistance and high peel strength.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure HDA0005112612060000011
    Figure HDA0005112612060000011
  • Figure HDA0005112612060000012
    Figure HDA0005112612060000012
  • Figure HDA0005112612060000021
    Figure HDA0005112612060000021
Patent Text Reader

Abstract

The invention discloses PEDOT: PSS-based conductive ink for heat transfer printing and a preparation method and application thereof, and belongs to the technical field of conductive materials and printing, the PEDOT: PSS-based conductive ink is prepared from the following raw materials in parts by mass: 100 parts of PEDOT: PSS, 1-10 parts of sorbitol, 0-1 part of a pH regulator, 0.2-10 parts of thermoplastic resin, 0.5-10 parts of GOPS, 0-1 part of a surfactant and 0-1 part of a thickener; wherein the weight ratio of the solid content of the PEDOT: PSS to the solid content of the thermoplastic resin is (2-8): (8-2). The PEDOT: PSS-based conductive ink disclosed by the invention can be transferred to various fabrics to form a fabric electrode with certain conductivity, excellent washing resistance and high peel strength.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of conductive materials and printing technology, and in particular to a PEDOT:PSS-based conductive ink for thermal transfer, and a preparation method and application thereof. Background Art

[0002] Thermal transfer inks have been widely used in pattern transfer on textiles and plastic surfaces. They have simple processes, fine patterns and good applicability. However, traditional thermal transfer inks, as described in application number CN202110728656, are mainly used for decoration, lack conductive functions, and are difficult to meet the needs of modern electronic textiles for intelligence and functionality. With the rapid development of fields such as smart fabrics, wearable devices and electronic skin, conductive thermal transfer inks have gradually become a research hotspot. However, existing conductive inks still have obvious deficiencies in conductivity, mechanical flexibility, stability and durability, which limits their promotion in practical applications.

[0003] As a conductive polymer, PEDOT:PSS occupies an important position in flexible electronic devices due to its unique properties. It has excellent conductivity, good optical transparency, outstanding mechanical flexibility, and easy processing, making it an ideal electrode material. Compared with traditional silver electrodes, PEDOT:PSS has significant advantages in cost, flexibility, and biocompatibility, especially in the fields of wearable devices and health monitoring. However, PEDOT:PSS has poor stability at high temperatures, is easy to degrade, and has insufficient adhesion and wear resistance, which limits its application in thermal transfer processes.

[0004] Therefore, developing a thermal transfer ink with excellent comprehensive properties such as conductivity, mechanical flexibility, stability and durability is a technical problem that needs to be urgently solved in this field. Summary of the invention

[0005] Purpose of the Invention

[0006] In order to overcome the above-mentioned shortcomings, the purpose of the present invention is to provide a PEDOT:PSS-based conductive ink for thermal transfer and its preparation method and application. The PEDOT:PSS-based conductive ink of the present invention can be transferred to various fabrics to form a fabric electrode with certain conductivity, excellent water-washing resistance and high peel strength.

[0007] Solution

[0008] To achieve the purpose of the present invention, the technical solution adopted by the present invention is as follows:

[0009] In a first aspect, the present invention provides a PEDOT:PSS-based conductive ink for thermal transfer, comprising the following raw materials in parts by weight: 100 parts of PEDOT:PSS, 1 to 10 parts by weight of sorbitol, 0 to 1 part of a pH adjuster, 0.2 to 10 parts of a thermoplastic resin, 0.5 to 10 parts of GOPS, 0 to 1 part of a surfactant, and 0 to 1 part of a thickener;

[0010] Wherein, the weight ratio of the solid content of PEDOT:PSS to the solid content of the thermoplastic resin is (2-8): (8-2).

[0011] Furthermore, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 2 to 8 parts by weight of sorbitol, 0 to 1 part of a pH adjuster, 0.5 to 10 parts of a thermoplastic resin, 1 to 5 parts of GOPS, 0.05 to 1 part of a surfactant, and 0.01 to 1 part of a thickener.

[0012] Furthermore, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 3 to 8 parts by weight of sorbitol, 0 to 1 part of a pH adjuster, 1.4 to 10 parts of a thermoplastic resin, 1 to 5 parts of GOPS, 0.05 to 1 part of a surfactant, and 0.01 to 1 part of a thickener.

[0013] Furthermore, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 3 to 6 parts by weight of sorbitol, 0 to 1 part of a pH adjuster, 1.4 to 9 parts of a thermoplastic resin, 2 to 4 parts of GOPS, 0.05 to 1 part of a surfactant, and 0.01 to 1 part of a thickener.

[0014] Optionally, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 3-6 parts by weight of sorbitol, 0-1 part of pH adjuster, 1.4-6 parts of thermoplastic resin, 2-4 parts of GOPS, 0.05-0.5 parts of surfactant, and 0.01-0.3 parts of thickener.

[0015] Optionally, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 1.4-5 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener.

[0016] Optionally, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 2-4 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener.

[0017] Optionally, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 3-4 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener.

[0018] Further, the weight ratio of the solid content of PEDOT:PSS to the solid content of the thermoplastic resin is (2-6):(4-8), optionally (3-5):(5-7), optionally (4-6):(6-4);

[0019] Optionally, the solid content in PEDOT:PSS is 1-5%, optionally 1-2%, optionally 1-1.5%, optionally 1.3%.

[0020] Optionally, the solid content of the thermoplastic resin is 40-70%, optionally 55-65%, optionally 59.5-61.5%.

[0021] And / or, the pH adjuster is used to adjust the pH of the mixed solution of PEDOT:PSS and sorbitol to 7-9.

[0022] Furthermore, the thermoplastic resin is selected from one or more of polypropylene resin, polyurethane resin and polytetrafluoroethylene resin; optionally, the thermoplastic resin is TPU resin.

[0023] Furthermore, the pH adjuster is a weak alkaline agent; optionally, the pH adjuster is selected from one or more of triethylamine, triethanolamine, dimethylethanolamine, sodium hydroxide aqueous solution, and ammonia water.

[0024] And / or, the surfactant is selected from one or more of anionic surfactants, cationic surfactants, zwitterionic surfactants, silicone surfactants and nonionic surfactants; optionally, the anionic surfactant is selected from one or more of FS-30, FS-3100, sodium dodecyl sulfonate, sodium dodecyl sulfate; optionally, the cationic surfactant is selected from hexadecyltrimethylammonium chloride; optionally, the zwitterionic surfactant is selected from betaines; optionally, the nonionic surfactant is selected from one or more of polyethylene glycol, Tween 20, Tween 80.

[0025] And / or, the thickener is selected from one or more of hydroxypropyl methylcellulose, carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl cellulose.

[0026] In a second aspect, a method for preparing the PEDOT:PSS-based conductive ink according to the first aspect is provided, comprising the following steps:

[0027] 1) Mix PEDOT:PSS and sorbitol according to the proportion;

[0028] 2) adding a pH adjuster to pH 7 to 9 in step 1);

[0029] 3) adding thermoplastic resin into step 2) and mixing;

[0030] 4) adding GOPS in step 3);

[0031] 5) Adding a surfactant and a thickener in step 4) to obtain a PEDOT:PSS-based conductive ink.

[0032] In a third aspect, a textile electrode is provided, comprising a conductive film prepared using the PEDOT:PSS-based conductive ink described in the first aspect or the PEDOT:PSS-based conductive ink prepared using the preparation method described in the second aspect.

[0033] In a fourth aspect, a method for preparing a fabric electrode is provided, comprising the following steps: transferring the PEDOT:PSS-based conductive ink described in the first aspect or the PEDOT:PSS-based conductive ink prepared by the preparation method described in the second aspect to the fabric by thermal transfer technology.

[0034] In a fifth aspect, a method for preparing a fabric electrode is also provided, comprising the following steps:

[0035] 1) taking the PEDOT:PSS-based conductive ink described in the first aspect or the PEDOT:PSS-based conductive ink prepared by the preparation method described in the second aspect, coating it on a base film, drying it, and forming a conductive film on the base film; optionally, the base film is a PET release film;

[0036] 2) applying hot melt adhesive on the surface of the conductive film in step 1), and drying to obtain a double-layer composite film;

[0037] 3) performing laser engraving on the double-layer composite film on the surface of the base film to obtain a double-layer composite film with a target pattern;

[0038] 4) The double-layer composite film with the target pattern on the base film is transferred to the fabric by thermal transfer to obtain a fabric electrode.

[0039] In a sixth aspect, a PEDOT:PSS-based conductive ink as described in the first aspect, or a PEDOT:PSS-based conductive ink prepared by the preparation method as described in the second aspect, or a fabric electrode as described in the third aspect, or a fabric electrode prepared by the preparation method as described in the fourth aspect is provided, and their application in the preparation of flexible electronics, smart textiles, health monitoring products, etc. is provided.

[0040] In order to solve the problems of the prior art, the present invention proposes a method for modifying PEDOT:PSS to adapt to the thermal transfer process. Specifically, D-sorbitol, thermoplastic resin and (3-glycidyl propoxy) trimethoxysilane (hereinafter referred to as GOPS) are added to PEDOT:PSS to improve its performance through material modification. D-sorbitol can improve the flexibility and conductivity of PEDOT:PSS. The introduction of thermoplastic resin significantly enhances the stretchability and wear resistance of the ink. GOPS improves the environmental stability and water resistance of PEDOT:PSS through cross-linking. These modification measures enable PEDOT:PSS to maintain good conductivity during the thermal transfer process and significantly improve its adhesion and durability on the fabric.

[0041] Beneficial Effects

[0042] (1) The PEDOT:PSS-based conductive ink of the present invention can be transferred to various fabrics to form a fabric electrode with certain conductivity, excellent water-washing resistance and high peel strength.

[0043] (2) The thermal transfer ink prepared by the modified PEDOT:PSS in the present invention performs well in the application on fabric electrodes, especially in terms of water resistance, wear resistance and adaptability to harsh environments. These characteristics make this type of fabric electrode have broad application prospects in the fields of smart clothing, health monitoring, environmental sensing, etc. The present invention not only opens up new possibilities for the application of PEDOT:PSS in thermal transfer technology, but also provides a theoretical basis and practical guidance for the further development of conductive thermal transfer inks, and has important scientific research and application value. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] One or more embodiments are exemplarily described by the pictures in the accompanying drawings, and these exemplary descriptions do not constitute limitations on the embodiments. The special word "exemplary" here means "used as an example, embodiment or illustrative". Any embodiment described as "exemplary" here is not necessarily interpreted as being superior or better than other embodiments.

[0045] Figure 1 The figure shows the change in tensile resistance of the fabric electrodes corresponding to Example 1 (4% sorbitol) and Comparative Example 1 (5% dimethyl sulfoxide) in Test Example 1 of the present invention, wherein sorbitol corresponds to the fabric electrode of Example 1 (4% sorbitol), and dimethyl sulfoxide corresponds to the fabric electrode of Comparative Example 1 (5% dimethyl sulfoxide).

[0046] Figure 2It is the corresponding resistance change of the electrode of the thermoplastic resin in the stretching process of Test Example 2 of the present invention with different dry weight mass fractions (the ratio of the solid content of TPU resin to the solid content in the system (the sum of the solid content of TPU resin and the solid content in PEDOT:PSS)); wherein, 0% represents the fabric electrode of Comparative Example 3 (0% TPU), 40% represents the fabric electrode of Example 3 (40% TPU), 60% represents the fabric electrode of Example 1 (60% TPU), and 80% represents the fabric electrode of Example 2 (80% TPU).

[0047] Figure 3 It is the resistance change of the electrode of the thermoplastic resin with different dry weight fractions (the ratio of the solid content of TPU resin to the solid content in the system (the sum of the solid content of TPU resin and the solid content in PEDOT:PSS)) of Test Example 2 of the present invention before and after 50 water washings, wherein 0% represents the fabric electrode of Comparative Example 3 (0% TPU), 20% represents the fabric electrode of Example 4 (20% TPU), 40% represents the fabric electrode of Example 3 (40% TPU), 60% represents the fabric electrode of Example 1 (60% TPU), and 80% represents the fabric electrode of Example 2 (80% TPU).

[0048] Figure 4 The morphology of the electrode of the thermoplastic resin with different dry weight fractions (the ratio of the solid content of TPU resin to the solid content in the system (the sum of the solid content of TPU resin and the solid content in PEDOT:PSS)) of Test Example 2 of the present invention after 50 water washings, wherein 0% TPU represents the fabric electrode of Comparative Example 3 (0% TPU), 20% TPU represents the fabric electrode of Example 4 (20% TPU), 40% TPU represents the fabric electrode of Example 3 (40% TPU), 60% TPU represents the fabric electrode of Example 1 (60% TPU), and 80% TPU represents the fabric electrode of Example 2 (80% TPU).

[0049] Figure 5 This is the morphology of the electrodes with different mass fractions of GOPS in Test Example 3 of the present invention after 50 water washings; wherein, 0% GOPS represents the fabric electrode of Comparative Example 3 (0% GOPS), 1% represents the fabric electrode of Example 5 (1% GOPS), 2% represents the fabric electrode of Example 1 (2% GOPS), 3% represents the fabric electrode of Example 6 (3% GOPS), 4% represents the fabric electrode of Example 7 (4% GOPS), and 5% represents the fabric electrode of Example 8 (5% GOPS).

[0050] Figure 6The resistance changes of electrodes with different mass fractions of GOPS in Test Example 3 of the present invention before and after 50 water washings are corresponding; wherein, 1% represents the fabric electrode of Example 5 (1% GOPS), 2% represents the fabric electrode of Example 1 (2% GOPS), 3% represents the fabric electrode of Example 6 (3% GOPS), 4% represents the fabric electrode of Example 7 (4% GOPS), and 5% represents the fabric electrode of Example 8 (5% GOPS).

[0051] Figure 7 It is the resistance change rate corresponding to the electrodes with different mass fractions of GOPS in Test Example 3 of the present invention before and after 50 water washings; wherein, the abscissa represents the mass fraction of GOPS, 1% represents the fabric electrode of Example 5 (1% GOPS), 2% represents the fabric electrode of Example 1 (2% GOPS), 3% represents the fabric electrode of Example 6 (3% GOPS), 4% represents the fabric electrode of Example 7 (4% GOPS), and 5% represents the fabric electrode of Example 8 (5% GOPS).

[0052] Figure 8 This is the effect of different GOPS mass fractions on the film conductivity of Test Example 3 of the present invention; wherein the abscissa represents the mass fraction of GOPS, 1% represents the fabric electrode of Example 5 (1% GOPS), 2% represents the fabric electrode of Example 1 (2% GOPS), 3% represents the fabric electrode of Example 6 (3% GOPS), 4% represents the fabric electrode of Example 7 (4% GOPS), and 5% represents the fabric electrode of Example 8 (5% GOPS).

[0053] Fig. 9 The tensile-resistance test result of 10,000 times of 40% tensile deformation of Test Example 4 of the present invention.

[0054] Fig.10 The compression-resistance test result of 10,000 times 80% compression deformation of Test Example 4 of the present invention.

[0055] Fig.11 The resistance change of the electrode of Test Example 4 of the present invention under the double 85 (temperature is 85° C., humidity is 85%) condition.

[0056] Fig.12 The resistance change of the electrode of Test Example 4 of the present invention after 10,000 frictions.

[0057] Fig.13This is the performance test of the wearable heater of Test Example 4 of the present invention, wherein a is the temperature change over time under different test voltages (5-10V); b is the temperature as a function of the input power density of the wearable heater; c is the temperature stability of the wearable heater for 5h under a continuous voltage of 8V; d is the thermal response result of the wearable heater when it is disconnected at 8V; e is the thermal response result of the wearable heater before and after 20 water washes; f is the infrared thermal image result of the head, hand, waist, bent arm, bent knee and foot of the wearable heater at a voltage of 12V. DETAILED DESCRIPTION

[0058] In order to make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the technical solution in the embodiments of the present invention will be described clearly and completely below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0059] In addition, in order to better illustrate the present invention, numerous specific details are provided in the specific embodiments below. It should be understood by those skilled in the art that the present invention can also be implemented without certain specific details. In some embodiments, raw materials, elements, methods, means, etc. well known to those skilled in the art are not described in detail, so as to highlight the main purpose of the present invention.

[0060] Unless explicitly stated otherwise, throughout the specification and claims, the term “comprise” or variations such as “include” or “comprising”, etc., will be understood to include the stated elements or components but not to exclude other elements or components.

[0061] The raw materials used in the present invention are all commercially available. For example, PEDOT:PSS is purchased from Heraeus PEDOT dispersion CLEVIOSPH1000 (solid content is 1.3%), and TPU resin is purchased from Shenzhen Tongtai Chemical Technology Co., Ltd., model U2101 (solid content is 59.5-61.5%, for the convenience of calculation, the solid content is 60%).

[0062] The method for preparing PEDOT:PSS-based thermal transfer conductive ink comprises the following steps:

[0063] 1) Weigh 10 g of PEDOT:PSS into a beaker, add 0.1-1 g of sorbitol, and stir thoroughly to obtain solution A;

[0064] 2) adding a certain amount of weak alkaline reagent to the solution A obtained in step 1) to make the entire solution weakly alkaline (pH about 7 to 9), and stirring thoroughly to obtain solution B;

[0065] 3) adding 0.14-0.9 g of thermoplastic resin (weight ratio of solid content of PEDOT:PSS to solid content of thermoplastic resin: (2-8): (8-2)) to liquid B obtained in step 2), and stirring thoroughly to obtain liquid C;

[0066] 4) Add 0.05-0.5 g of GOPS to the liquid C obtained in step 3) (the mass ratio of liquid C to GOPS is 10:0.05-1), and stir thoroughly for a certain period of time to obtain liquid D;

[0067] 5) Add 0.005-1 g of a surfactant and a thickener to the liquid D obtained in step 4), and stir thoroughly to obtain a PEDOT:PSS-based conductive ink for thermal transfer.

[0068] Embodiment 1,

[0069] 1) Weigh 10 g of PEDOT:PSS (solid content 1.3%) in a beaker, add 0.4 g of sorbitol (sorbitol accounts for about 4%), and stir thoroughly to obtain liquid A;

[0070] 2) adding 0.015-0.02 g of a weakly alkaline reagent to the solution A obtained in step 1) to make the entire solution weakly alkaline (pH about 7-9), and stirring thoroughly to obtain solution B;

[0071] 3) Add 0.325 g of TPU resin (U2101, solid content 60%) to the liquid B obtained in step 2) (can be recorded as 60% TPU, 60% TPU refers to the mass fraction of the solid content in the TPU resin in the solid content of the liquid C (the sum of the solid content of the TPU resin and the solid content in the PEDOT:PSS), calculated as = 0325 × 0.6 / (0325 × 0.6 + 10 × 0.013), that is, the mass ratio of the solid content in the PEDOT:PSS to the solid content of the TPU resin is 4:6), and stir thoroughly to obtain liquid C;

[0072] 4) Add 0.2 g GOPS (referred to as 2% GOPS) to the solution C obtained in step 3), and stir thoroughly for a certain period of time to obtain solution D;

[0073] 5) Add 0.05 g FS-30 (surfactant) and 0.02 g carboxymethyl cellulose to the D solution obtained in step 4), and stir thoroughly to obtain a PEDOT:PSS-based thermal transfer conductive ink.

[0074] Example 2

[0075] The difference between Example 2 and Example 1 is that in step 3), the amount of TPU resin (U2101) added is 0.867 g (recorded as 80% TPU), and the remaining steps and raw material addition ratios are the same.

[0076] Example 3

[0077] The difference between Example 3 and Example 1 is that in step 3), the amount of TPU resin (U2101) added is 0.144 g (recorded as 40% TPU), and the remaining steps and raw material addition ratios are the same.

[0078] Example 4

[0079] The difference between Example 4 and Example 1 is that in step 3), the amount of TPU resin (U2101) added is 0.054 g (recorded as 20% TPU), and the remaining steps and raw material addition ratios are the same.

[0080] Example 5

[0081] The difference between Example 5 and Example 1 is that in step 4), the amount of GOPS added is 0.1 g (recorded as 1% GOPS), and the remaining steps and raw material addition ratios are the same.

[0082] Example 6

[0083] The difference between Example 6 and Example 1 is that in step 4), the amount of GOPS added is 0.3 g (recorded as 3% GOPS), and the remaining steps and raw material addition ratios are the same.

[0084] Example 7

[0085] The difference between Example 7 and Example 1 is that in step 4), the amount of GOPS added is 0.4 g (denoted as 4% GOPS), and the remaining steps and raw material addition ratios are the same.

[0086] Example 8

[0087] The difference between Example 8 and Example 1 is that in step 4), the amount of GOPS added is 0.5 g (recorded as 5% GOPS), and the remaining steps and raw material addition ratios are the same.

[0088] Comparative Example 1

[0089] The difference between this comparative example 1 and Example 1 is that 0.4 g of sorbitol (a dopant) in step 1) is replaced with 0.5 g of dimethyl sulfoxide (a conventional dopant), and the remaining steps and raw material addition ratios are the same. That is, only the dopant is changed on the basis of Example 1, which is recorded as 5% dimethyl sulfoxide.

[0090] Comparative Example 2

[0091] The difference between this comparative example 2 and example 1 is that sorbitol is not added in step 1), and the remaining steps and raw material addition ratios are the same, that is, no dopant (before doping) is added.

[0092] Comparative Example 3

[0093] The difference between this comparative example 3 and example 1 is that in step 3), no TPU resin (U2101) is added, and the remaining steps and raw material addition ratios are the same. It is recorded as 0% TPU.

[0094] Comparative Example 4

[0095] The difference between this comparative example 4 and example 1 is that in step 4), GOPS is not added, and the remaining steps and raw material addition ratios are the same, which is recorded as 0% GOPS.

[0096] Fabric electrode preparation example

[0097] The PEDOT:PSS-based thermal transfer conductive inks of the above-mentioned examples and comparative examples were respectively prepared into fabric electrodes, and relevant tests were performed on them.

[0098] Fabric electrode preparation process:

[0099] S1. Use a blade coater to evenly coat the PEDOT:PSS-based conductive ink on the PET release film, and put it into an oven for drying to obtain a conductive film;

[0100] S2. After the conductive film is completely dried, a layer of hot melt adhesive is coated on the surface of the conductive film using a scraper coater, and the film is placed in an oven for drying to obtain a double-layer composite film;

[0101] S3, laser engraving the prepared double-layer composite film according to the designed CAD drawing (wherein the PET release film is not cut by laser), and after laser engraving, tearing off the non-patterned part from the PET release film to obtain the target pattern;

[0102] S4. The conductive pattern is transferred from the PET release film to the fabric through a thermal transfer process to obtain a fabric electrode.

[0103] According to the above method, the PEDOT:PSS-based conductive ink prepared in the above examples and comparative examples was used to prepare fabric electrodes, which were referred to as fabric electrodes prepared in examples 1 to 8 and comparative examples 1 to 4, respectively. The following related tests were performed respectively.

[0104] Test Example 1: Effect of Sorbitol

[0105] Conductivity test

[0106] Conductivity test method: The doped PEDOT:PSS solution was spin-coated onto a glass sheet treated with plasma oxygen and heated on a heating table at 160°C for 20 minutes to obtain a PEDOT:PSS film. After cooling, the sheet resistance of the PEDOT:PSS film was measured using a four-probe tester, model RTS-9. The film thickness was measured using a step profiler, and the formula σ=1 / (R□*h)

[0107] Wherein, σ represents the conductivity (unit: Siemens / meter, S / cm), R□ represents the square resistance measured by four-probe (unit: ohm, Ω), and h represents the film thickness measured by the step profiler (unit: centimeter, cm).

[0108] The conductivity of the doped PEDOT:PSS solutions prepared in step 1 of Example 1, Comparative Example 1 and Comparative Example 2 was tested respectively. The results are shown in Table 1.

[0109] Table 1 Effect of different dopants on the conductivity of PEDOT:PSS

[0110] Conductivity Example 1 (PEDOT:PSS solution doped with 4% sorbitol) 697.7S / cm Comparative Example 1 (PEDOT:PSS solution doped with 5% dimethyl sulfoxide) 706.6S / cm Comparative Example 2 (before doping) 0.6S / cm

[0111] The results show that, compared with Comparative Example 2, Example 1 doped with sorbitol and Comparative Example 1 doped with dimethyl sulfoxide can increase the conductivity of the PEDOT:PSS solution from 0.6 S / cm to more than 690 S / cm.

[0112] Tensile resistance test

[0113] The stretching-resistance test method is: the PEDOT:PSS-based thermal transfer conductive ink prepared in Example 1 and Comparative Example 1 is used to prepare fabric electrodes according to the above-mentioned fabric electrode preparation method, wherein steps S3 and S4 are slightly different: the obtained double-layer composite film is cut into 1cm*5cm rectangular electrodes by laser cutting, and then the square electrodes are thermally transferred to the middle part of the fabric whose size is larger than the square electrodes, and silver paste is applied to both ends of the short side of the prepared fabric electrode by masking method, and the test sample can be obtained after the silver paste is cured. The sample to be tested is placed in the Nanosheng stretching test system model S-P2 for stretching operation, and the BlueBird nanoampere ammeter is used at both ends of the fabric electrode to measure the change of current during the stretching process. By calculation, the change of resistivity during the stretching process can be obtained.

[0114] The fabric electrodes prepared in Example 1 and Comparative Example 1 were subjected to a tensile resistance test. The results are as follows: Figure 1The results show that the fabric electrode of Example 1 (PEDOT:PSS solution doped with 4% sorbitol) can still maintain a certain conductivity when the tensile deformation reaches 100%. However, the fabric electrode of Comparative Example 1 (PEDOT:PSS solution doped with 5% dimethyl sulfoxide) completely loses its conductivity when the tensile deformation is about 24%.

[0115] It is shown that the PEDOT:PSS solution of the present invention can improve the stretchability of the fabric electrode after doping with sorbitol, and has a significant effect on improving the plasticity and conductivity of the PEDOT:PSS ink. The sorbitol used in Example 1 can increase the flexibility of PEDOT:PSS through hydrogen bonds, reduce the glass transition temperature (Tg), and keep the prepared film soft and elastic at low temperatures. Therefore, sorbitol not only enhances the mechanical properties of the film, but also reduces its brittleness. In contrast, the conventional dopant (dimethyl sulfoxide (DMSO)) used in Comparative Example 1 failed to show similar performance, resulting in the fabric electrode prepared in Comparative Example 1 becoming fragile after thermal transfer. The inventor speculates that DMSO may improve its conductivity by regulating the interaction between PEDOT and PSS, but cannot change the flexibility of the material, resulting in the PEDOT film prepared by it being easily brittle under stress.

[0116] Test Example 2: Effect of Thermoplastic Resin

[0117] To investigate the effect of thermoplastic resin on fabric electrodes, the following tests were performed:

[0118] Tensile resistance test

[0119] Referring to the stretching-resistance test method of Test Example 1, the stretching-resistance test was performed on the fabric electrodes prepared in Examples 1 to 3 and Comparative Example 3, respectively. The results are as follows: Figure 2 .

[0120] The results show that when only the proportion of thermoplastic resin is adjusted, as the mass fraction of TPU resin (model U2101) (thermoplastic resin) increases, the stretchability of the corresponding electrode also increases.

[0121] Water washing test

[0122] The PEDOT:PSS-based thermal transfer conductive inks prepared in Examples 1 to 4 and Comparative Example 3 with different proportions of thermoplastic resin were respectively prepared into fabric electrodes and subjected to water washing experiments. The test method was as follows:

[0123] S1. Cut the obtained double-layer composite film into 3 cm × 3 cm square electrodes using a laser cutting machine, and then thermally transfer the square electrodes to the middle part of the fabric whose size is larger than that of the square electrodes;

[0124] S2. Place the sample in S1 into an automatic drum washing machine for washing test. The washing standard is ISO

[0125] 105-C10:2006, the washing mode is standard, and the entire washing project takes 30 minutes, including 2 water injections, 2 washes, and 2 spins. One complete run of the washing machine in standard mode is considered 1 wash, and the second, third, and 50th washes are performed in the same manner;

[0126] S3. After each sample is washed, it is dried in a 60℃ oven for 30 minutes, cooled to room temperature, and the resistance of the fabric electrode after different washing times is tested. The results are as follows: Figure 3 , Figure 4 .

[0127] Figure 3 The results show that the resistance of the fabric electrode of Comparative Example 3 (without adding thermoplastic resin (0% TPU)) increased by 7 times after the first water washing, and after the second water washing, the resistance increased to a state of almost no conductivity. Figure 4 The electrode morphology of "0% TPU" is consistent with that of Figure 4 It can be observed that a large number of cracks appeared on the surface of the fabric electrode of "0% TPU" (Comparative Example 3), which led to a sharp increase in resistance and even caused the electrode to lose conductivity. This result shows that the PEDOT:PSS-based thermal transfer ink cannot meet the requirements of the thermal transfer process when only sorbitol is used without adding thermoplastic resin.

[0128] Figure 3 The results also show that the resistance of the fabric electrodes of Example 4 (20% TPU) and Example 3 (40% TPU) also increased sharply, and the resistance of the fabric electrode of Example 3 (40% TPU) increased later than that of Example 4 (0% TPU). This may be because the stretchability of the electrode increases with the increase of the thermoplastic resin content, which is consistent with the Figure 2 The trend is consistent with that shown in the figure. However, in Example 1 (60% TPU) and Example 2 (80% TPU), the TPU resin content added is relatively high, and the phenomenon of a sharp increase in resistance does not occur. Figure 4 It can also be seen that there are almost no cracks on the electrode surface of Example 1 (60% TPU) and Example 2 (80% TPU), while the cracks of Example 4 (20% TPU) and Example 3 (40% TPU) gradually decrease with the increase of TPU content. This shows that the thermoplastic resin with a dry weight fraction of 60% TPU (the ratio of the solid content of TPU resin to the total solid content of the system (the solid content of TPU resin and the solid content of PEDOT:PSS)) is sufficient to provide sufficient stretchability to adapt to the deformation of the fabric during 50 washings.

[0129] Since thermoplastic resin itself is an insulating material, it will have a negative impact on the conductivity of PEDOT:PSS-based thermal transfer ink. Therefore, the amount of thermoplastic resin added needs to be controlled within an appropriate range (50% to 70% dry weight fraction) to ensure that the conductive properties of the ink are not affected.

[0130] In the thermal transfer ink based on PEDOT:PSS, the thermoplastic resin introduced in the present invention plays multiple roles. It not only enhances the flexibility of the ink, enabling it to better adapt to various substrates, but also significantly improves the adhesion between the ink and the substrate, thereby improving the durability of the electrode. In addition, the thermoplastic resin also improves the processing properties of the ink, optimizing its fluidity and shape stability during the thermal transfer process. It also improves the thermal stability of PEDOT:PSS at high temperatures, reduces the risk of thermal degradation, and enhances the mechanical properties of the film, including tensile strength and tear resistance.

[0131] Test Example 3: Effect of (3-glycidylpropoxy)trimethoxysilane (GOPS)

[0132] To study the effect of GOPS on fabric electrodes, the following tests were performed:

[0133] Water washing test

[0134] The PEDOT:PSS-based thermal transfer conductive inks prepared in Example 1, Examples 5 to 8, and Comparative Example 4 with different GOPS ratios were respectively prepared into fabric electrodes and subjected to water washing experiments. The test method was the same as the water washing test method in Test Example 2. The results are as follows: Figure 5 , Figure 6 , Figure 7 .

[0135] Figure 5 The results show that the PEDOT:PSS layer of the fabric electrode of Comparative Example 1 (0% GOPS) has completely fallen off during the first water washing, causing the electrode to lose resistance.

[0136] Figure 6 , 7 The results show that with the increase of GOPS mass fraction, the resistance change rate of the fabric electrode gradually decreases after 50 washes, which is consistent with Figure 5 This is consistent with the reduction in the degree of electrode shedding. Figure 5 In the figure, with the increase of GOPS mass fraction, the morphology of the electrode after 50 water washings is more complete and there are fewer blank areas, indicating that the addition of GOPS helps to improve the water resistance of the electrode.

[0137] However, this does not mean that the higher the GOPS content in the ink formula, the better. Although GOPS can improve the water resistance of the electrode, excessive GOPS may affect the conductivity and processing properties of the ink. Therefore, when designing the ink formula, it is necessary to balance the amount of GOPS added to achieve the best performance.

[0138] Conductivity test

[0139] Referring to the test method of conductivity in Test Example 1, the conductivity tests were performed on the fabric electrodes prepared in Example 1, Examples 5 to 8, and Comparative Example 4 (using a four-probe tester, model RTS-9, to measure the square resistance of the fabric electrodes). The results are as follows: Figure 8 .

[0140] Figure 8 The effect of different GOPS mass fractions on the conductivity of the film was demonstrated. The results showed that as the GOPS mass fraction increased, the conductivity of the film gradually decreased. Figure 7 From the data in , we can know that the optimal addition amount of GOPS should be between 2% and 4% to ensure that the electrode maintains good water washability while also maintaining high conductivity.

[0141] The present invention adds (3-glycidyl propoxy) trimethoxy silane (GOPS) to PEDOT:PSS to improve its waterproof performance, mainly because the epoxy groups of GOPS can react with the hydroxyl groups in PEDOT:PSS to form a stable three-dimensional cross-linked network, which effectively blocks the penetration of water. In addition, the hydrophobic silane groups of GOPS form an additional waterproof barrier in the film, increase the surface tension, and reduce the wettability of water molecules. At the same time, GOPS improves the chemical stability of the PEDOT:PSS film, making it more resistant to hydrolysis reactions, thereby maintaining its waterproof properties.

[0142] In summary, the sorbitol, thermoplastic resin and GOPS of the present invention each play an indispensable role in the PEDOT:PSS-based thermal transfer conductive ink. The synergistic effect of the thermoplastic resin and GOPS significantly improves the waterproof performance of the fabric electrode prepared by the PEDOT:PSS-based thermal transfer conductive ink, making it suitable for electronic devices and sensors in humid environments or underwater applications.

[0143] Test Example 4

[0144] Tensile and compressible testing

[0145] The PEDOT:PSS-based thermal transfer ink of Example 1 was used to prepare a 5×1 cm rectangular electrode (the preparation method thereof refers to the preparation of the fabric electrode, except that steps S3 and S4 are slightly different: in S3, a laser cutting machine is used to cut the obtained double-layer composite film into 5×1 cm rectangular electrodes, and then the square electrodes are thermally transferred to the middle part of the fabric whose size is larger than the square electrodes). The rectangular electrodes were placed on a tensile testing machine for 10,000 stretching-resistance tests with a 40% tensile deformation and 10,000 compression-resistance tests with a 80% compression deformation, where R0 is the initial resistance before the test. The resistivity change was detected and calculated, and the results are as follows: Fig. 9 , Fig.10 .

[0146] Fig. 9 The results show that after the electrode is stretched 10,000 times under 40% tensile deformation, the resistance value of the electrode increases by about 6.7 times, and it can still play the role of an electrode.

[0147] Fig.10 The results show that the resistance value of the electrode remains almost unchanged after the electrode is compressed 10,000 times at 80% compression deformation.

[0148] It is explained that the thermal transfer ink based on PEDOT:PSS of the present invention can make electrodes on clothes, which can meet the deformation of the human body during the process of dressing and undressing.

[0149] Environmental stability test

[0150] The PEDOT:PSS-based thermal transfer ink of Example 1 was used to prepare a 3×3 cm square electrode (the preparation method thereof refers to the preparation of the fabric electrode, except that steps S3 and S4 are slightly different: in S3, a laser cutting machine is used to cut the obtained double-layer composite film into a 3×3 cm square electrode, and then the square electrode is thermally transferred to the middle part of the fabric whose size is larger than the square electrode). The square electrode was placed in a constant temperature and humidity chamber, the temperature was set to 85°C, the humidity was set to 85%, and the resistance change was detected. The experimental results are as follows: Fig.11 shown.

[0151] Fig.11 The results show that the resistance value of the electrode changes very little under the double 85 (temperature is 85℃, humidity is 85%) conditions, and only increases by 60Ω, indicating good environmental stability.

[0152] Wear resistance test

[0153] The PEDOT:PSS-based thermal transfer ink of Example 1 was selected to prepare a 4.2 cm circular electrode (the preparation method thereof refers to the preparation of the fabric electrode, except that the steps S3 and S4 are slightly different: in S3, a laser cutting machine is used to cut the obtained double-layer composite film into a 4.2 cm circular electrode, and then the circular electrode is thermally transferred to the middle part of the fabric whose size is larger than the circular electrode), and the wear resistance test was carried out according to ISO 12947-2:2016 standard. The abrasive is wool fabric, the friction strength is 9 kPa, and it is prepared to rub 10,000 times. The resistance is measured every 100 times for the first 1,000 times, and the resistance is measured every 1,000 times after 1,000 times. The results are as follows Fig.12 shown.

[0154] Fig.12 The results show that the resistance of the electrode remains almost unchanged during the first 1,000 frictions, and after 10,000 frictions, the resistance only increases by 4 times, indicating excellent wear resistance.

[0155] Heating performance test

[0156] The PEDOT:PSS-based thermal transfer ink of Example 1 was selected to prepare a 3×3 cm square heater (the preparation method refers to the preparation of the fabric electrode, except that steps S3 and S4 are slightly different: in S3, a laser cutting machine is used to cut the obtained double-layer composite film into 3×3 cm square electrodes, and then the square electrodes are thermally transferred to the middle part of the fabric whose size is larger than the square electrodes) (the preparation method refers to the preparation of the fabric electrode, except that steps S3 and S4 are slightly different: in S3, a laser cutting machine is used to cut the obtained double-layer composite film into 4.2 cm circular electrodes, and then the circular electrodes are thermally transferred to the middle part of the fabric whose size is larger than the circular electrodes. Subsequently, a layer of conductive silver paste is applied on both sides of each electrode using a masking technique. After the silver paste is completely cured, a layer of conductive copper foil is covered on its surface, and a firm electrical connection is ensured between the copper foil and the silver paste by tapping, so as to obtain a wearable heater.) The heater was powered on using an external power supply at an ambient temperature of 25°C, and the temperature and image of the heater were tested using a handheld infrared imager. The experimental results are as follows Fig.13 shown.

[0157] Fig.13 The results show that:

[0158] Fig.13 a shows the wearable heater’s ability to reach a steady-state temperature within 60 seconds at different voltages, which demonstrates its fast response characteristics and reliability in practical applications.

[0159] Fig.13b shows that as the input voltage increases from 5V to 10V, the stable temperature of the wearable heater increases from 35.7℃ to 64.0℃ accordingly. When the heater temperature exceeds 50℃, its ultra-low power density is about 0.03W / cm 2 , which confirms that in daily operation, the heater consumes very low energy.

[0160] Fig.13 c shows that the wearable heater can maintain a saturated temperature of around 50°C for up to 5 hours, which demonstrates the excellent durability of the heater in long-term stable heating.

[0161] Fig.13 d shows the stability of the saturation temperature of the heater when the voltage is cycled on and off at 8 V, further demonstrating the stability of the heater.

[0162] Fig.13 e shows that the wearable heater can still reach the saturation temperature even after 20 water washings, which demonstrates the excellent water-wash resistance of the heater.

[0163] Fig.13 f shows that the temperature of various parts of the heater exceeds 40°C, which indicates that within the safe voltage range of the human body, the heater can generate heat stably and can adapt to the deformation caused by human movement in daily life.

[0164] The results show that the developed wearable heater not only has a quick response and low energy consumption, but also has good durability and water resistance, and can work stably at a human safety voltage to meet the needs of daily use. In addition, the fabric electrodes prepared by the PEDOT:PSS-based thermal transfer conductive ink of the present invention have excellent durability, which enables them to maintain stable performance in long-term applications.

[0165] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A PEDOT:PSS-based conductive ink for thermal transfer, characterized in that: Including the following raw materials by mass: PEDOT:PSS 100 parts, sorbitol 1-10 parts by weight, pH adjuster 0-1 part, thermoplastic resin 0.2-10 parts, GOPS 0.5-10 parts, surfactant 0-1 part, thickener 0-1 part; Wherein, the weight ratio of the solid content of PEDOT:PSS to the solid content of the thermoplastic resin is (2-8): (8-2).

2. The PEDOT:PSS-based conductive ink according to claim 1, characterized in that: The invention comprises the following raw materials in parts by weight: 100 parts of PEDOT:PSS, 2 to 8 parts by weight of sorbitol, 0 to 1 part of a pH regulator, 0.5 to 10 parts of a thermoplastic resin, 1 to 5 parts of GOPS, 0.05 to 1 part of a surfactant, and 0.01 to 1 part of a thickener; Optionally, the raw materials include the following parts by weight: 100 parts of PEDOT:PSS, 3-8 parts by weight of sorbitol, 0-1 part of pH adjuster, 1.4-10 parts of thermoplastic resin, 1-5 parts of GOPS, 0.05-1 part of surfactant, and 0.01-1 part of thickener; Optionally, the raw materials include the following parts by weight: 100 parts of PEDOT:PSS, 3-6 parts by weight of sorbitol, 0-1 part of pH adjuster, 1.4-9 parts of thermoplastic resin, 2-4 parts of GOPS, 0.05-1 part of surfactant, and 0.01-1 part of thickener; Optionally, the raw materials are included in the following weight parts: 100 parts of PEDOT:PSS, 3-6 parts by weight of sorbitol, 0-1 parts of pH adjuster, 1.4-6 parts of thermoplastic resin, 2-4 parts of GOPS, 0.05-0.5 parts of surfactant, and 0.01-0.3 parts of thickener; Optionally, the raw materials are included in the following weight parts: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 1.4-5 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener; Optionally, the raw materials are included in the following weight parts: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 2-4 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener; Optionally, the raw materials are included in the following weight proportions: 100 parts of PEDOT:PSS, 4 parts by weight of sorbitol, 0-0.5 parts of pH adjuster, 3-4 parts of thermoplastic resin, 2-4 parts of GOPS, 0.1-0.5 parts of surfactant, and 0.02-0.2 parts of thickener.

3. The PEDOT:PSS-based conductive ink according to claim 1 or 2, characterized in that: The weight ratio of the solid content of PEDOT:PSS to the solid content of the thermoplastic resin is (2-6):(4-8), optionally (3-5):(5-7), optionally (4-6):(6-4); Optionally, the solid content of PEDOT:PSS is 1-5%, optionally 1-2%, optionally 1-1.5%, optionally 1.3%; Optionally, the solid content of the thermoplastic resin is 40-70%, optionally 55-65%, optionally 59.5-61.5%; And / or, the pH adjuster is used to adjust the pH of the mixed solution of PEDOT:PSS and sorbitol to 7-9.

4. The PEDOT:PSS-based conductive ink according to any one of claims 1 to 3, characterized in that: The thermoplastic resin is selected from one or more of polypropylene resin, polyurethane resin and polytetrafluoroethylene resin; optionally, the thermoplastic resin is TPU resin.

5. The PEDOT:PSS-based conductive ink according to any one of claims 1 to 4, characterized in that: The pH regulator is a weak alkaline reagent; optionally, the pH regulator is selected from one or more of triethylamine, triethanolamine, dimethylethanolamine, sodium hydroxide aqueous solution, and ammonia water; And / or, the surfactant is selected from one or more of anionic surfactants, cationic surfactants, zwitterionic surfactants, silicone surfactants and nonionic surfactants; optionally, the anionic surfactant is selected from one or more of FS-30, FS-3100, sodium dodecyl sulfonate, sodium dodecyl sulfate; optionally, the cationic surfactant is selected from hexadecyltrimethylammonium chloride; optionally, the zwitterionic surfactant is selected from betaines; optionally, the nonionic surfactant is selected from one or more of polyethylene glycol, Tween 20, Tween 80; And / or, the thickener is selected from one or more of hydroxypropyl methylcellulose, carboxymethyl cellulose, methyl cellulose, and sodium carboxymethyl cellulose.

6. A method for preparing a PEDOT:PSS-based conductive ink according to any one of claims 1 to 5, characterized in that: The steps include: 1) Mix PEDOT:PSS and sorbitol according to the proportion; 2) adding a pH adjuster to pH 7 to 9 in step 1); 3) adding thermoplastic resin into step 2) and mixing; 4) adding GOPS in step 3); 5) Adding a surfactant and a thickener in step 4) to obtain a PEDOT:PSS-based conductive ink.

7. A fabric electrode, characterized in that: It comprises a conductive film prepared by using the PEDOT:PSS-based conductive ink described in any one of claims 1 to 5 or the PEDOT:PSS-based conductive ink prepared by the preparation method described in claim 6.

8. A method for preparing a fabric electrode, characterized in that: The method comprises the following steps: transferring the PEDOT:PSS-based conductive ink according to any one of claims 1 to 5 or the PEDOT:PSS-based conductive ink prepared by the preparation method according to claim 6 to the fabric by means of thermal transfer technology.

9. A method for preparing a fabric electrode, characterized in that: The steps include: 1) taking the PEDOT:PSS-based conductive ink according to any one of claims 1 to 5 or the PEDOT:PSS-based conductive ink prepared by the preparation method according to claim 6, coating it on a base film, drying it, and forming a conductive film on the base film; optionally, the base film is a PET release film; 2) applying hot melt adhesive on the surface of the conductive film in step 1), and drying to obtain a double-layer composite film; 3) performing laser engraving on the double-layer composite film on the surface of the base film to obtain a double-layer composite film with a target pattern; 4) The double-layer composite film with the target pattern on the base film is transferred to the fabric by thermal transfer to obtain a fabric electrode.

10. A PEDOT:PSS-based conductive ink according to any one of claims 1 to 5, or a PEDOT:PSS-based conductive ink prepared by the preparation method according to claim 6, or a fabric electrode according to claim 7, or a fabric electrode prepared by the preparation method according to claim 8 or 9, characterized in that: Applications in the preparation of flexible electronics, smart textiles, health monitoring products, etc.

Citation Information

Patent Citations

  • A thermal transfer ink and its preparation method

    CN113354981B